The Influence of Transformational Leadership, Progressive Discipline, and Affective Commitment on Managerial Performance in the Fintech Sector - Abd. Rasyid Syamsuri; Elperida Juniarni Sinurat; Tukimin (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study explores the impact of transformational leadership and progressive discipline on managerial performance in Indonesia’s fintech sector, mediated by affective commitment, to forge an integrative framework that connects leadership practices, disciplinary mechanisms, and emotional bonds to enhanced effectiveness in this nascent digital domain. Adopting a quantitative approach, primary data were collected via structured questionnaires and observations from 167 branch managers, sampled using Slovin’s formula supplemented by secondary sources from company records and academic literature; analyses employed SPSS for validity and reliability assessments and SmartPLS 4 for hypothesis testing. Findings indicate that transformational leadership and progressive discipline significantly elevate affective commitment and performance, with the latter acting as a potent predictor and mediator, explaining 59.8% of performance variance; intriguingly, a direct negative effect of transformational leadership on performance highlights contextual boundaries in dynamic industries. By synthesizing these elements, the research enriches human resource management and organizational behavior scholarship in an underexplored fintech context, though its specificity to Sumatran branches limits generalizability, warranting future longitudinal studies across sectors and integration of factors like organizational culture or digital adaptability.